Conductivity effect on broadband dipole antenna with split ring resonators - Kedze, Kam Eucharist; Wang, Heesu; Park, Ikmo (2019 13th International Congress on Artificial Materials for Novel Wave Phenomena, Metamaterials 2019, 2019)
In this paper, a composite broadband dipole antenna printed with different conductivities is presented. The antenna is composed of two identical split ring resonators (SRRs) surrounding each arm of a dipole element. Each arm of the dipole and the SRRs are printed on the top and bottom sides of a thin dielectric substrate to give the antenna flexibility. The compact flexible antenna with overall dimensions of 74.8 mm × 10 mm × 0.254 mm (0.473λ ×0.063λ × 0.0016λ at 1.9 GHz) produces linearly polarized omnidirectional radiations. Characteristics of the antenna, including reflection coefficient, gain, and radiation efficiency to different conductivities, are investigated.
Keywords: Dielectric substrates; Flexible antennas; Linearly polarized; Omnidirectional radiation; Radiation efficiency; Split ring resonator